Resistência a corrosão da camada martensitica formada na superfície do aço inoxidável ferrítico 409 tratado por SHTPN - Assumpção, Roberto Luís de (2013)
Stainless steels are widely used on chemical, petrochemical, nuclear, energy generation, biomedical and food processing industries. In general, stainless steels present good corrosion resistance. However, the application of these materials can be restrained by the hardness and the corrosion resistance. Usually, high strength steels present high carbon content and martensitic structure, what can consequently cause a reduction on corrosion resistance. On the other hand, high corrosion resistance steels present low hardness and weak wear properties. Thereby, many solutions have been made to improve simultaneously wear properties and corrosion resistance of these materials, specially related to the introduction of nitrogen on the surface, through plasma nitriding, ion implantation and SHTPN (Solution Heat Treatment after Plasma Nitriding) processes. The aim of this paper is to determine SHTPN parameters that can form nitrogen martensite on the surface of AISI 409 stailess steel, as well as the evaluation of its corrosion resistance. It was verified an improve on corrosion resistance conditions of SHTPN treated samples. Aditionally, there was an improve on mechanical resistance showed by hardness profiles.